Vital Relations : Modernity and the Persistent Life of Kinship - McKinnon, Susan, 1949- (Book collections on Project MUSE., 2013)
"For more than 150 years, theories of social evolution, development, and modernity have been unanimous in their assumption that kinship organizes simpler, "traditional," pre-state societies but not complex, "modern," state societies. And these theories have been unanimous in their presupposition that within modern state-based societies kinship has been relegated to the domestic domain, has lost its economic and political functions, has retained no organizing force in modern political and economic structures and processes, and has become secularized and rationalized. Vital Relations challenges these notions. It will be of interest to anyone who wishes to gain a different perspective on the concept of modernity itself, and on the place of kinship and "family" in modern life."--pub. desc.